Obtenção, caracterização e avaliação pré-clínica da segurança de nanopartículas lipídicas e poliméricas contendo o antiangiogênico sunitinibe para aplicação tópica ocular: um estudo comparativo - Souza, Leonardo Gomes (2014)
Corneal vascularization (CV) is a common cause of visual impairment and blindness. Sunitinib (SUB) is an antiangiogenic agent that has demonstrated a significant reduction of VC in rabbits. Incorporation of SUB in nanosystems can increase your corneal retention and decrease P-glycoprotein resistance and it conversion to inactive isomer E (trans) when the drug is exposed to light. In this work, liposomes (LIPO), polymeric nanospheres (NE) and solid lipid nanoparticles (SLN) containing SUB was developed. Systems presented particle size between 70 and 200 nm and PdI below 0.3 and a high encapsulation efficiency. NE had a greater capacity to incorporate sunitinib when compared to liposomes and SLN. This system had drug loading of 4.3% while LIPO and SLN showed 2.87% and 1.66%, respectively. Release profile of sunitinib was different in three developed systems. Liposomes sustained drug release greater than that observed for the polymer nanospheres and solid lipid nanoparticles in the same period. SLN showed higher corneal retention of SUB when compared to other systems. Within thirty minutes corneal retention of SUB from SLN (15 µg/cm2) was more than twice that observed for liposomes (6.8 µg/cm2). NE also showed corneal retention of SUB (12.7 µg/cm2) superior to liposomes. Spectroscopic studies of electron paramagnetic resonance (EPR) comparing liposomes and SLN demonstrated that SLN are more flexible than liposomes. These studies also indicated that sub is located in the lipid bilayer of liposomes near the phospholipid-water interface, leading to increased rigidity. In SLN the drug is also probably located near the lipid-water interface, altering the crstaline organiation of the lipids and increased fluidity. These results justify the faster release profile observed for SUB from SLN and higher corneal retention of drug from these nanosystems. Employing alternative methods to the use of animals for determining the safety of the formulations, all three formulations developed showed no potential for ocular irritation in tests of bovine corneal opacity and permeability test method (BCOP), in the evaluation of hemolytic potential and in the test in chorioallantoic membrane of chicken egg (HET-CAM). Among the systems developed in this work containing SUB, SLN seems to present a greatest potential for clinical application in the treatment of VC.